Reality Therapy: an Approach for Handling the Psycho-Social Challenges Confronting Divorcees in Nigeria - Yusuf Jemilat; Muraina Kamilu Olanrewaju (Universitas Mathla'ul Anwar Banten, 2022)
The house is the bedrock of any society. Risky domestic therefore results in risky society. Divorce in marriages and the consequent impact, a part of which might be anger, inferiority complex, mistrust, stigmatization, discrimination, emotional overload, loneliness, guilt, depression and so forth, are most of the maximum urgent problems going through human society nowadays. However, as painful as this reality is, this situation absolute confidence requires the attention of professional counsellors. This paper therefore evaluations the psycho-social demanding situations confronting divorcees and the counselling approach for handling it. In so doing, efforts are geared closer to highlighting the idea of reality remedy and its applications in coping with the psycho-social challenges confronting divorcees in Nigeria.